Effectiveness of microinsurance during and after a disaster - Ali, Arshad; Mahmood, Asad; Gul, Shahnila (JNRD - Journal of Natural Resources and Development, 2014)
This research looks at the effectiveness of microinsurance services during and after a disaster and at disaster management as an effective tool for community betterment. A detailed review has been done on available research and case studies. Unfortunately, underdeveloped countries suffer due to a lack of finances during and after a disaster. Developed countries are usually not ready for any disaster at government and public levels. A disaster affected country will also be keen for financial help from donor agencies and other counties. Microinsurance would be very helpful during any disaster to overcome the financial needs at the community level. Microinsurance is a practice that can share the financial liability with the affected population during a disaster. There is no trend in Pakistan for community based microinsurance for certain reasons, although there are very good examples available for review in the region. These include microinsurance services based on community microinsurance models such as SEWA (Gujarat), Weather-Index-based insurance (Ethiopia) and Crop insurance against typhoons (Philippine). These have played a vital role in disaster risk transfer during and after disasters. This study will identify the implementation and outcome of microinsurance in Pakistan during a disaster and understand how much beneficial microinsurance would be for the betterment and recovery of affective community on an urgent basis.